2016
DOI: 10.1111/sji.12419
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain Alters Adiponectin Receptor 1 Expression on Adipose Tissue‐Resident Helios+ Regulatory T Cells

Abstract: Adipose tissue produces multiple mediators that modulate the immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Interestingly, impaired adiponectin signalling has been reported at both receptor and post-receptor levels. For example, adiponectin receptor 1 has been shown to be expressed on adipose tissue-resident Tregs, and this expression is negatively correlated with epididymal fat mass even in the absence of significant changes in serum adiponectin [40]. Although dWAT-Tregs have not been investigated, it is possible that in our model, increased adiposity also associates with changes in local immunoregulation via reduced adiponectin sensitivity of dWAT-resident Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, impaired adiponectin signalling has been reported at both receptor and post-receptor levels. For example, adiponectin receptor 1 has been shown to be expressed on adipose tissue-resident Tregs, and this expression is negatively correlated with epididymal fat mass even in the absence of significant changes in serum adiponectin [40]. Although dWAT-Tregs have not been investigated, it is possible that in our model, increased adiposity also associates with changes in local immunoregulation via reduced adiponectin sensitivity of dWAT-resident Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin-deficient mice developed worse EAE and greater central nervous system (CNS) inflammation, demyelination and axon injury together with a defect in Treg cell number and function (80). In this context, Ramos-Ramírez et al showed that adipose tissue resident Treg cells expressed higher levels of adiponectin receptor 1 (AdipoR1) than Treg cells in the spleen, and adipoR1 expression on adipose tissue Helios + Treg cells was negatively correlated with epididymal fat (81). In conclusion, these data suggest that mediators involved in the regulation of food intake have affect Treg cell metabolism.…”
Section: Environment and Treg Cellsmentioning
confidence: 99%
“…T regs can be identified in tissue with expression of Foxp3 in CD3+ CD4+ cells (Ramos-Ramírez et al, 2016). Regulatory T cells have been deemed a crucial part of the immune system due to their aid in the control of autoimmunity and allergies (Feuerer et al, 2009).…”
Section: Lymphocytes and Visceral Adipose Tissuementioning
confidence: 99%